The Use of Thematic Progression in the Journal Artcile of Ã¢â‚¬Å“U-JETÃ¢â‚¬Â - Hati Puji Lestari, Suci; Mujiyanto, Januarius; Saleh, Murshid (English Education Journal, 2019)
This study aimed to evaluate thematic progressions pattern in students’ journal article written by undergraduate students. This study employed qualitative research in the form of written discourse analysis. The documentation observation sheet is used to analyze the patterns apperead in the article written by students. Out of 10 students chosen as the sample. The results of this study revealed that from the three patterns, zigzag pattern is the most frequently used by the students. The second is re-iteration pattern and the last one is multiple theme pattern. It showed that the students can employed the patterns though they never learn about systemic functional linguistics before. But, the results of their writing is not really coherence. Because the lack of thematic progression pattern used. For the consistency, there are several students who already consistent in their writing, though the rest is still not consistent. However, they never learn about this. Therefore, it can be said that understanding the thematic progression is important because it can make the writing effective and coherence.